Web-Based Library Application With Brute Force Algorithm Implementation In The Search Module - Afirin; Sri Lestanti (JOSAR (Journal of Students Academic Research), 2021)
The library is a means that can support the student learning process so that it must be well organized. However, the data management in the library of SMK Negeri 1 Bakung is still in the books. Data management includes visitor data, book data, and loan transaction data. Besides, students take a long time when looking for the books they need and cannot find out what books are available if they do not come directly to the library. Based on the problems that have been mentioned, a web-based library application is needed. The application is created using the Codeigniter Framework and the Mysql database as data storage by applying the brute force algorithm in the search module. Test results from 10 trials using several search keywords, The brute force algorithm gets an average running time of 0.1631 seconds. Search time speed is influenced by the number of words entered and the form of words in Indonesian and English.